2020
DOI: 10.1111/cpr.12833
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes secreted by chronic hepatitis B patients with PNALT and liver inflammation grade ≥ A2 promoted the progression of liver cancer by transferring miR‐25‐3p to inhibit the co‐expression of TCF21 and HHIP

Abstract: Objectives The current study aimed to investigate the mechanism by which exosomes secreted by CHB patients with PNALT and liver inflammation grade (≥A2) affected the development of liver cancer. Materials and methods Gene expression was assessed by RT‐PCR, Western blotting and immunohistochemistry. CCK‐8, colony formation, transwell, scratch‐wound and flow cytometry assays were used to detect cell viability, proliferation, apoptosis and metastasis. The interaction of TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In this study, PEG-IFN α -2b showed faster inhibition of inflammation, which may also be related to our above inference. The occurrence of inflammatory reaction is a complicated pathological process, in which IFs are dominant, and cytokines such as monocytes and eosinophils are also involved [ 29 ]. As aforementioned, PEG-IFN α -2a works only in liver and blood and does not affect the activity cycle of cells, so its anti-inflammatory response is not as significant as PEG-IFN α -2b, an IFN gene involved in the cell life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, PEG-IFN α -2b showed faster inhibition of inflammation, which may also be related to our above inference. The occurrence of inflammatory reaction is a complicated pathological process, in which IFs are dominant, and cytokines such as monocytes and eosinophils are also involved [ 29 ]. As aforementioned, PEG-IFN α -2a works only in liver and blood and does not affect the activity cycle of cells, so its anti-inflammatory response is not as significant as PEG-IFN α -2b, an IFN gene involved in the cell life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that the expression of HHIP is significantly reduced in AGS cells where miR-199b-5p is not significantly expressed. Studies have shown that HHIP is the target gene of miR-25-3p in hepatocellular carcinoma ( 32 ). We speculate that the connection between miR-199b-5p and HHIP is regulated by potential factors in AGS cells, but this requires further mechanism research to explore.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles have reported that miRNAs can promote cell proliferation and migration. Ouyang et al demonstrated that miR‐25‐3p can promote the proliferation of HepG2.2.15 cells 30 . Zhu et al indicated that miR‐671‐5p could facilitate PCa cell proliferation and migration in vitro and in vivo 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Ouyang et al demonstrated that miR‐25‐3p can promote the proliferation of HepG2.2.15 cells. 30 Zhu et al indicated that miR‐671‐5p could facilitate PCa cell proliferation and migration in vitro and in vivo . 31 Li et al found that miR‐301a promotes cell proliferation and migration in lung tumorigenesis by suppressing Runx3.…”
Section: Discussionmentioning
confidence: 99%